STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DAN GURU DALAM MEMBENTUK KARAKTER SISWA - Iskandar, Iskandar (STKIP Subang, 2017)
This study aims to describe the strategy of principals, teachers, in the character formation of students in primary schools. The research approach used is qualitative with case study type. The research instrument is the researcher himself. Data collection using in-depth interviews, participant observation and documentation. Research respondents are snow-ball. Data analysis technique using Creswell model (2014). Validity of data used criteria of credibility, transferability, dependability, and komfirmabilitas. The conclusion of the research is the principal's strategy in shaping the character of the students with the philosophy of leadership, exemplary, discipline, instructional leadership, quality leadership, as well as teacher empowerment and education. Teacher strategy is exemplary, habituation, and touch of heart. Parent and community strategies are effective communication and effective partnerships.